EFEKTIVITAS DINAS PEKERJAAN UMUM DALAM PEMELIHARAAN JALAN DI KOTA MAKASSAR - Puspa, Andi Asindah; Parawu, Hafiz Elfiansyah; Taufik, Ahmad (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to find out how effective the Public Works Department is in maintaining Makassar City roads. The data collection techniques used were observation, interviews and documentation. Data analysis techniques through reduction, data presentation, drawing conclusions/evaluation. The validity of the data is obtained from source triangulation, technical triangulation and time triangulation. The results of the research show that the timeliness of the Public Works Department in the road maintenance program in the city of Makassar is that as long as the program is implemented it is in accordance with the time specified before the road maintenance program is carried out. The Public Works Department has tried to achieve the objectives of the road maintenance program in Makassar City with specific objectives in the form of regular monitoring and evaluation for work on damaged roads. The real changes felt by the Public Works Department and the community with the road maintenance program in the city of Makassar have been well realized because of the many positive impacts of the program.